1979
DOI: 10.23986/afsci.72011
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of 15N and 14C into amino acids of bacterial and protozoal protein in the rumen of the cow on urea-rich feed

Abstract: Abstract. The utilization of the non-protein nitrogen and carbon of feed by rumen microorganisms for the synthesis of protein was studied by administering [U-14 C] sucrose and 15 NH 4 C1 to a cow on urea-rich, low-protein feed. By studying the labelling of the protozoa and bacteria and the amino acids isolated from them at intervals up to 48 hours afterwards, it was found that the bacteria synthesized amino acids from nonprotein nitrogen much more rapidly and effectively than the protozoa. Also the labelling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…In the faeces of 0-and ULP-cows the contents of glutamic acid, methionine, isoleucine and tyrosine were greater than with Nor P-cows, whereas the amounts of proline, glycine, histidine and arginine were smaller. In a feeding experiment with 15 NH 4 C1 the slowest incorporation of ammonium nitrogen was into histidine, proline, arginine and glycine with both bacteria and protozoa in the rumen of the ULP-cows (Syväoja and Kreula 1979). The amino acid composition of NorP-cows' faeces was almost the same as that in the studies of Tamminga (1975).…”
Section: Discussionsupporting
confidence: 47%
“…In the faeces of 0-and ULP-cows the contents of glutamic acid, methionine, isoleucine and tyrosine were greater than with Nor P-cows, whereas the amounts of proline, glycine, histidine and arginine were smaller. In a feeding experiment with 15 NH 4 C1 the slowest incorporation of ammonium nitrogen was into histidine, proline, arginine and glycine with both bacteria and protozoa in the rumen of the ULP-cows (Syväoja and Kreula 1979). The amino acid composition of NorP-cows' faeces was almost the same as that in the studies of Tamminga (1975).…”
Section: Discussionsupporting
confidence: 47%
“…It should, however, be pointed out that in some experiments alanine accumulation was shown in Bacteriodes amylophilus which contained no detectable alanine dehydrogenase (Jenkinson et al 1979). Other investigators, using 15N-labelled urea or ammonium chloride to study ammonia incorporation into whole bacteria in vitro, have also found alanine to be one of the most highly labelled amino acids (Shimbayashi et al 1975;Syvaoja & Kreula, 1979). Salter et al (1979) found relatively high labelling of alanine in whole bacteria in vivo after adding 15N-labelled urea to the rumen and postulated that this was due to the action of transaminases, the amino group coming from glutamate or aspartate.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed protozoal preparations containing holotrich ciliates have been used in studies on the nature and properties of rumen protozoal protease (96,187,(222)(223)(224) and metabolism of specific amino acids including lysine (190), tryptophan (95), arginine, proline, ornithine (196,198), citrulline (198), threonine (197), and methionine (160,197). Mixed populations have also been used to examine the range of anmino acids taken up (11,186), the factors affecting this incorporation (10, 120), and de novo amino acid synthesis (225,232). The rumen protozoal fraction has a range of transaminase activities (27, 28, 131) and will incorporate exogenous urea added to the culture medium (181).…”
Section: Nitrogen Metabolismmentioning
confidence: 99%